Distribuição das teneurinas na região orofacial de ratos durante o desenvolvimento embrionário e pós-natal - Dias, Camila Ambrósio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Teneurins (TENs) are constituted by four homologous proteins (teneurin 1 to 4), initially described in mammals. TENs are similar to proteins of the extracellular matrix denominated tenascins. Thus, TENs are expressed mainly during central nervous system development. Interestingly, TEN expression is preserved throughout species. Previous studies pointed out that her expression can also be noted in non-neural tissues, primarily during the morphogenesis of some organs and tissues. Some studies have reported the expression of TENs in the anterior region of chicken and mice embryos, suggesting a possible role of this family in orofacial development. The present study is a detailed analysis of the distribution of the four family members of the TENs (TEN1-4) in tissues and organs of the orofacial region of rodents through immunohistochemical techniques. Therefore, rats at different orofacial development stages were used to assess the participation of TENs in the development of the orofacial territory. Immunohistochemical analysis of TENs was also performed during regeneration of the dentin-pulp complex, particularly the behavior of odontoblasts during experimental injury in rat molars. Furthermore, we analyzed TENs expression in human dental pulp through immunohistochemical and conventional RT-PCR methods. The data showed that TEN2 immunoreactivity is present in odontoblasts during differentiation, and this remained present in mature teeth. Showed also that TEN1 is discretely expressed during odontoblast differentitation. TEN2 imunoreactivity in odontoblasts was modulated by pulp inflammation. Gene expression and immunohistochemical methods confirmed the presence of TEN2 in human dental pulp. In conclusion, the present study is the first to confirm the presence of TEN2 in rat and human odontoblasts. In addition, TEN2 can be modulated in odontoblasts by inflammation process induced in rat molar tooth

As Teneurinas (TENs) são constituídas por quatro proteínas homólogas (teneurina 1 a 4), descritas inicialmente em mamíferos. As TENs apresentam similaridade com uma proteína da matriz extracelular denominada tenascinas. Deste modo, as TENs apresentam expressão principalmente durante o desenvolvimento do sistema nervoso central. Interessantemente, a expressão das TENs é preservada ao longo das espécies. Estudos anteriores apontam que sua expressão também pode ser observada em tecidos não neuronais, principalmente durante a morfogênese de alguns órgãos e tecidos. Alguns estudos relataram a expressão das TENs na região anterior de embriões de aves e ratos, sugerindo um possível papel dessa família no desenvolvimento orofacial. O presente estudo é uma análise detalhada da distribuição dos quatro membros da família das TENs (TEN1-4) em tecidos e órgãos da região orofacial de roedores através de técnicas de imuno-histoquímica. Portanto, ratos em diferentes estádios de desenvolvimento orofacial foram utilizados para avaliar a participação de TENs no desenvolvimento do território orofacial. A análise imuno-histoquímica das TENs também foi realizada durante a regeneração do complexo polpa-dentina, em particular, no comportamento dos odontoblastos frente uma lesão experimental dos molares de ratos. Além disso, analisamos a expressão das TENs na polpa dentária humana através de métodos de RT-PCR e imuno-histoquímica convencionais. Os dados mostraram que a imunorreatividade da TEN2 está presente nos odontoblastos durante sua diferenciação, e esta se manteve presente nos dentes maduros. Mostraram também que a TEN1 é discretamente expressa durante a diferenciação dos odontoblastos. A imunorreatividade da TEN2 nos odontoblastos foi modulada pela inflamação da polpa. Expressão gênica...
Keywords: Ratos; Odontoblastos; Imunohistoquímica; Polpa dentária; Rats